Securing Consumer Rights: Ethical and Legal Measures against Advertisements that Violate Advertising Procedures - Dijan Widijowati; Sergiy Denysenko (APPTHI, 2023)
Abstract. Advertising is an integral part of modern consumer culture, shaping consumer behavior and influencing purchasing decisions. However, concerns have arisen regarding advertisements that violate established advertising procedures, such as false claims, deceptive practices, and manipulative tactics. This paper explores the legal measures available to protect consumers from such advertisements and secure their rights. It emphasizes the importance of consumer rights in maintaining a fair marketplace and examines the consequences of advertising violations on consumer trust and decision-making. The research adopts a comprehensive methodology, combining normative and empirical juridical approaches, to analyze the existing legal framework and propose improvements. The study highlights the responsibilities of advertisers, advertising companies, and advertising media in ensuring compliance with ethical standards. It also discusses the implications of sanctions for violations and explores the resolution of consumer disputes through specialized bodies or the court system. The findings contribute to ongoing discussions on consumer protection in advertising and aim to foster a fair and transparent marketplace that respects consumers’ rights Keywords: Advertising procedures, consumer rights, misleading advertisements, legal measures Abstrak. Periklanan merupakan bagian integral dari budaya konsumen modern, membentuk perilaku konsumen dan memengaruhi keputusan pembelian. Namun, muncul kekhawatiran mengenai iklan yang melanggar prosedur periklanan yang telah ditetapkan, seperti klaim palsu, praktik penipuan, dan taktik manipulatif. Makalah ini mengeksplorasi langkah-langkah hukum yang tersedia untuk melindungi konsumen dari iklan semacam itu dan mengamankan hak-hak mereka. Ini menekankan pentingnya hak-hak konsumen dalam menjaga pasar yang adil dan memeriksa konsekuensi dari pelanggaran iklan pada kepercayaan konsumen dan pengambilan keputusan. Penelitian ini mengadopsi metodologi yang komprehensif, menggabungkan pendekatan yuridis normatif dan empiris, untuk menganalisis kerangka hukum yang ada dan mengusulkan perbaikan. Studi ini menyoroti tanggung jawab pengiklan, perusahaan periklanan, dan media periklanan dalam memastikan kepatuhan terhadap standar etika. Dibahas pula implikasi sanksi atas pelanggaran dan pendalaman penyelesaian sengketa konsumen melalui badan khusus atau sistem pengadilan. Temuan berkontribusi pada diskusi berkelanjutan tentang perlindungan konsumen dalam periklanan dan bertujuan untuk mendorong pasar yang adil dan transparan yang menghormati hak-hak konsumen Kata kunci: Prosedur periklanan, hak konsumen, iklan yang menyesatkan, tindakan hukum